PEMETAAN KARAKTERISTIK PASIR SUNGAI DI WILAYAH BANYUWANGI SELATAN - Anisa, Nindi; Rifqi, Mirza Ghulam (Politeknik Negeri Banyuwangi, 2025)
Banyuwangi Regency is a regency located at the southern coastal tip of the island of Java. Banyuwangi has abundant natural resources, especially in the southern region, one of which is river sand as a building material. This research was conducted to find out how the characteristics and quality of river sand in 6 sub-districts located in the southern region. This research uses SNI and ASTM as the basis of research, the things studied include: specific gravity, volume weight, sieve analysis, sand absorption water content, mud content, and sand moisture. The results showed that the average fineness modulus (FM) is included in the gradation zone 2 with FM values of 2.50-3.00, which is classified as moderately coarse sand. The specific gravity of sand in Pesanggaran, Gambiran, and Tegalsari 2 (North) sub-districts does not meet the standard requirements (2.4-2.7). In the volume weight test, all sand samples from seven sub-districts met the requirements. The infiltration water content varied, with the smallest value in Tegalsari 1 (east) sub-district at 1.45% and the highest value in Purwoharjo sub-district at 2.92%. Mud content was generally below 5%, except in Kecamatan Pesanggaran where it reached 5.45% (dry) and 5.30% (wet). Sand moisture in Siliragung, Bangorejo, and Tegalsari 1 (East) sub-districts met the requirement of no more than 2%. The sand cleanliness test for organic matter showed that the sand in Bangorejo sub-district was free of organic matter, while the sand in the other 6 sub-districts was indicated to contain organic matter.